Location-arc routing problem: Heuristic approaches and test instances - Lopes, Rui Borges
Location-routing is a branch of locational analysis that takes into account distribution aspects. The locationarc routing problem (LARP) considers scenarios where the demand is on the edges rather than being on the nodes of a network (usually a road network is assumed). Examples of such scenarios include locating facilities for postal delivery, garbage collection, road maintenance, winter gritting and street sweeping. This paper presents some heuristic approaches to tackle the LARP, as well as some proposals for benchmark instances (and corresponding results). New constructive and improvement methods are presented and used within different metaheuristic frameworks. Test instances were obtained from the capacitated arc routing problem (CARP) literature and adapted to address the LARP